תשובה:
# 1 / p ^ 2-1 / q ^ 2 = 2sqrt2 #…..# (p <q) #.
רמז: # (x-y) ^ 2 = x ^ 2 + y ^ 2-2xy = x ^ 2 + 2xy + y ^ 2-4xy #
# => (x-y) ^ 2 = (x + y) ^ 2-4xy #
בבקשה תשתמש '^' במקום ' * '. # i.e.x ^ 2 ל #x ^ 2 ולא x * 2
הסבר:
אני חושב שהמשוואה הריבועית שלך היא
# 3x ^ 2-12x + 6 = 0 #.
להשוות ל # ax ^ 2 + bx + c = 0 #,אנחנו מקבלים
# a = 3, b = -12 ו- c = 6 #
אם השורשים של equn זה. הם #p ו- q #, לאחר מכן
# p + q = -b / a ו- pq = c / a #
# i.e.p + q = - (12) / 3 = 4 ו- pq = 6/3 = 2 #
עכשיו, # (P = 2q ^ 2) = (q + p) (q-p)) (pq) ^ 2 # # / p ^ 2-1 / q ^ 2 = (q ^ 2-p ^ 2),….# (p <q) #
# (=) 1 / p ^ 2-1 / q ^ 2 = (4) sqrt (q-p) ^ 2)) / 2 ^ 2 = sqrt (q-p) ^ 2 #
# => 1 / p ^ 2-1 / q ^ 2 = sqrt (q + p) ^ 2-4pq = = sqrt (4 ^ 2-4) 2 #
# => 1 / p ^ 2-1 / q ^ 2 = sqrt (16-8) = sqrt8 = 2sqrt2 #….# (p <q) #
# 3x ^ 2-12x + 6 = 0 #
# => x ^ 2 - 4x + 2 = 0 #
שורשים, #x = (- b + -qqrt (b ^ 2-4ac)) / (2a) #
# x = (4 + -sqrt (16-4 * 1 * 2)) / (2) #
# x = (4 + -sqrt (8)) / (2) = (4 + -2sqrt (2)) / (2)
# x = (2 + -2sqrt (2)) #
למצוא, # 1 / p ^ 2 - 1 / q ^ 2 #
# => (1 / p + 1 / q) (1 / p-1 / q) #
(1) (1 / (2 + 2sqrt (2)) 1 / (2-2sqrt (2)) (1 / (2 + 2sqrt)
2 (2-2sqrt (2)) (2 + 2sqrt) (2)))) ((2-2sqrt) (2-2sqrt) (2-2sqrt) (2) 2 (2 + 2sqrt) 2) 2 (2) 2 (2)) (2 + 2sqrt (2)))) #
(2) 2 (2 + 2)) / (2-2sqrt (2)) (2 + 2sqrt) (2))) () (2) 2 (2 + 2sqrt (2)))) #
# (4) (4 (4sqrt2)) / ((4-8)) ^ 2) # #
# => ((4 (-4sqrt2)) / (- 4) ^ 2) # #
# => (- sqrt2) #